Dietary Resistant Starch Regulates Bile Acid Metabolism by Modulating the FXR/LRH-1 Signaling Pathway in Broilers - Zhenxin Wang; Chunyan Zhan; Yingying Zhang; Lin Zhang; Jiaolong Li; Tong Xing; Liang Zhao; Jianfei Wang; Feng Gao (Agriculture, 2023)
This study aimed to investigate the effects of dietary corn-resistant starch on the bile acid metabolism of broilers. In total, 80, 1-day-old male broilers were randomly distributed into two groups fed either the basic normal corn–soybean diet or a diet supplemented with 40 g/kg of corn-resistant starch. The results showed that dietary supplementation of 4% corn-resistant starch increased the F/G during the periods from 21 to 42 d. Resistant starch supplementation reduced the lipid levels in plasma, and the contents of total bile acids were increased with the altered bile acid profile in the ileum. A diet with corn resistant starch decreased the enzyme contents of the classical pathway of bile acid synthesis and activated the signaling pathway of FXR/LRH-1 in the liver. A decreased abundance of Clostridium cluster XIVa was found in the ileal digesta of the resistant starch group, and its abundance was negatively correlated with the level of lithocholic acid. In summary, the RS was effective at reducing broiler plasma and liver lipid levels, which was probably due to the change in bile acid synthesis and reabsorption capacities. These findings provided a unique landscape of the relationship between bile acid metabolism and resistant starch in broilers.